2010
DOI: 10.1016/j.bbagen.2009.12.005
|View full text |Cite
|
Sign up to set email alerts
|

The ferritin superfamily: Supramolecular templates for materials synthesis

Abstract: Members of the ferritin superfamily are multi-subunit cage-like proteins with a hollow interior cavity. These proteins possess three distinct surfaces, i.e. interior and exterior surfaces of the cages and interface between subunits. The interior cavity provides a unique reaction environment in which the interior reaction is separated from the external environment. In biology the cavity is utilized for sequestration of irons and biomineralization as a mechanism to render Fe inert and sequester it from the exter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
209
0
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(217 citation statements)
references
References 134 publications
2
209
0
6
Order By: Relevance
“…Recently it was shown that the hollow structure of apoferritin can be exploited as an excellent reaction vessel for nanoscale synthesis of dierent minerals. Up to date many compounds have been synthesised within this protein cage [1,2] and potential applications in electronics and biomedicine were discussed [35]. The ferritin-mineral complex with a magnetite (or a maghemite) as a core mineral, is called magnetoferritin (MFer) [1].…”
Section: Introductionmentioning
confidence: 99%
“…Recently it was shown that the hollow structure of apoferritin can be exploited as an excellent reaction vessel for nanoscale synthesis of dierent minerals. Up to date many compounds have been synthesised within this protein cage [1,2] and potential applications in electronics and biomedicine were discussed [35]. The ferritin-mineral complex with a magnetite (or a maghemite) as a core mineral, is called magnetoferritin (MFer) [1].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, magnetite and/or maghemite have been synthesized in vitro inside apoferritin to produce a novel material known as magnetoferritin. Further development of this biomimetic way of nanosynthesis within the ferritin cavity 181,182 has allowed the production of ferritin with various cores, as illustrated in Figure 10. In general, HSF is used as the starting material for preparation of apoferritin, which is used as a nanoreactor.…”
Section: Synthetic Ferritinsmentioning
confidence: 99%
“…Each ferritin molecule is made of 24 subunits, which are self-assembled, in a noncovalent fashion, into a cagelike nanostructure. [25] Such an intriguing architecture of ferritins has attracted previous research interest in their use as nanoreactors to synthesize nanomaterials. [26][27][28] Their potential in the field of optical imaging, however, has seldom been studied.…”
mentioning
confidence: 99%